Nanotechnology and Neutraceuticals - Swarnali Das Paul; Divya Dewangan (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2016)
This paper provides an insight of some of the growing number of nano-applications being researched and commercialized in nutraceuticals. Recently, number of applications in dairy and food processing, preservation, packaging and development of functional foods have become based on nanotechnology. Several critical challenges, including discovering of beneficial compounds, establishing optimal intake levels, developing adequate food delivering matrix and product formulation including the safety of the products need to be addressed. In addition the potential negative effects of nanotechnology- based delivery systems on human health need to be considered.